(untitled) (Medicine Today, 2014)
Drug addiction and drug abuse, chronic or habitual use of any chemical substance to alter states of body or mind for other than medically warranted purposes. Addiction is more often now defined by the continuing, compulsive nature of the drug use despite physical and/or psychological harm to the user and society and includes both licit and illicit drugs, and the term "substance abuse" is now frequently used because of the broad range of substances (including alcohol and inhalants) that can fit the addictive profile. Psychological dependence is the subjective feeling that the user needs the drug to maintain a feeling of well-being; physical dependence is characterized by tolerance (the need for increasingly larger doses in order to achieve the initial effect) and withdrawal symptoms when the user is abstinent. There are a lot of effects of drug addiction to the economy, society, and family. Drug addiction affects individual’s physical and mental health. Drug addicts are burden for a family and society. It is a great challenge for all nations of the world to prevent drug addiction. This article reviews the effects of drug addiction in details. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17927 Medicine Today 2013 Vol.25(2): 84-89